Implementasi Pengembangan SDM untuk Meningkatkan Reputasi UIN Raden Fatah Palembang - Muji Gunarto; Paizurahman Paizurahman (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
This study takes the theme of implementing human resource development to improve the Raden Fatah State Islamic University of Palembang's reputation. The background to this problem is that there are still obstacles in lecturer development related to further studies and the formation of the need for the number of lecturers that is not appropriate. This research method is qualitative with the subjects of the employees of UIN Raden Fatah Palembang. The data analysis technique used in this research is descriptive statistical analysis techniques. The study results were that at the time of the recruitment of UIN Raden Fatah, a centralized admission process was carried out at the central government by submitting to the Indonesian Ministry of Religion if it wanted to carry out the process of admitting new teaching staff. However, this system has weaknesses because the center does not understand what is happening in the field so that decisions do not match what is expected. The lecturers' qualifications for the number of lecturers or doctoral lecturers below 30%, and the rest are Masters lecturers